Активність тирозинових протеїнфосфатаз у клітинах слизової оболонки шлунка за умов стрес-індукованих виразкових уражень - Богданова, О.В.; Кузьменко, Л.І.; Остапченко, Л.І.; Кучеренко, М.Є. (Видавничий дім "Академперіодика" НАН України, 2007)
Protein tyrosine phosphatase activities in plasma membranes and cytosol of stomach mucosa cells of rats are studied under conditions of stress-induced gastric lesions development and during the first — fifth days of their recovering. A significant decrease in protein tyrosine phosphatase activities is established. The treatment with omeprazole, a proton pump inhibitor with antioxidant features, caused the stabilizing result only immediately after stressing.